POLITIK EKOLOGI : KEBIJAKAN PENANGANAN BANJIR ROB DI PEKALONGAN - Herlina Muzanah Zain; Madi Ramadhan; iqbal Aidar Idrus; Angella Rosha Pangestu (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2023)
This study is about the strategy for dealing with tidal flooding in the Pekalongan coastal area through various good policies contained in regulations and forms of cooperation with various stakeholders. Tidal floods, which are still occurring today, have become the driving force for the birth of new policies. This study aims to find out the main causes of the failure of policy implementation in handling tidal floods. Qualitative approach Research using the method of collecting data from literature review, review of government documents and other relevant articles as a research design. The results of this study indicate that the policy for handling tidal floods is influenced by the factor of weak law enforcement in disposing of batik waste which pollutes the environment which is considered to exacerbate tidal floods, not yet synchronizing with other supporting policies. The regional government has not been synchronized with other supporting policies in order to accelerate the handling of tidal floods, such as the municipal government carrying out large-scale developments in the midst of their efforts to deal with tidal floods. Increasing mutual understanding between the government and the community to protect the environment together because tidal floods are also caused by climate change factors which are nothing but human activities.